Views and experiences of eating disorders treatments in East Asia: a meta-synthesis - See Heng Yim; Ulrike Schmidt (Journal of Eating Disorders, 2024)
Abstract Introduction Although there have been qualitative meta-syntheses on experiences of eating disorders treatments, there is a paucity of syntheses specifically examining the perspectives and experiences of eating disorders treatments (ED) in East Asia (EA). Such synthesis could facilitate a better understanding of culture-specific perspectives and experiences. This review complements a quantitative scoping review published on ED treatments in EA (Yim & Schmidt, 2023), where most interventions reviewed focused on cognitive behavioural therapy (CBT) and internet interventions. The present meta-synthesis summarises stakeholders’ views on treatments and to synthesise clinical and research recommendations. Method A systematic search of five databases and a citation search were conducted to identify relevant studies and data were analysed using thematic synthesis. Out of the 301 studies found, a total of 12 papers were included in the analysis. Results A diverse range of treatments, such as family therapy, paediatric/psychiatric inpatient care, CBT, and counselling, were discussed. Three overarching themes were identified: Delineating Physical and Psychological Recovery; ‘I am not alone in this battle’; and Barriers to Change. The themes further delve into the various obstacles to recovery, including financial concerns and limited access to professionals and services. Culture-specific factors include family obligations and promoting family harmony. Balancing interdependence and independence from one’s family, as well as understanding family body ideals versus broader societal body ideals, are important considerations in ED interventions. Discussion Some themes paralleled other qualitative syntheses, highlighting improved family relationships, perceived authoritarianism in treatments, and financial barriers. The review extends beyond the previous findings, revealing nuanced factors like family roles, cultural values, and norms. Clinical recommendations include incorporating family context in treatment and considering cultural influences on body image ideals. Capacity building through telemedicine and increased training is essential for advancing ED treatment in East Asia. Continued research is needed to better understand and treat people affected by ED in EA.